Tinjauan Ketepatan Kode Diganosis Tuberkulosis Paru Pasien Rawat Jalan di Rumah Sakit SHL Pandeglang - Rahelia Putri; Lily Widjaja; Dina Sonia; Daniel Happy Putra (Yayasan Literasi Sains Indonesia, 2024)
In coding activities, medical recorders and health information are needed who master how to give disease codes according to ICD-10 and actions according to ICD-9 CM so that the resulting code has accuracy according to the diagnosis or action given. One of the most frequently used coding accuracy is accuracy in coding for Pulmonary Tuberculosis. One of the important things is how to describe the accuracy of the Outpatient Pulmonary Tuberculosis diagnosis code at SHL Pandeglang Hospital. This study was shown to determine the accuracy of the diagnosis code for Outpatient Pulmonary Tuberculosis at SHL Pandeglang Hospital. This research method uses a descriptive method with a quantitative approach. The sample of this study was taken by saturated sampling technique. Data were taken using interviews and observations. The results of the study of 122 medical records obtained accuracy of 93 (76.2%) files and inaccuracy of 29 (23.8%) files. Based on the identification of factors causing the inaccuracy of the diagnosis code, there are 4 factors, namely the man factor: occurs due to the lack of accuracy of the coder in coding, the workload of the coder, and the lack of training for coders with non-RMIK backgrounds. Material factors: the unavailability of the Medical Dictionary (Dictionary of Medical Terminology) and the absence of an abbreviated list of diagnoses (standard). Machine factors: damage to the computer, software hangs, and computers that are too old. Method factor: incomplete SPO diagnosis coding.